PEMURIDAN PAULUS KEPADA TIMOTIUS: ANALISA HISTORIS KRITIS 2 TIMOTIUS 3:14-17 - Aritonang, Udur Ernita; Sianipar, Magel Haens (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
The relationship between Paul and Timothy in the New Testament is an important relationship for the development of early Christianity. Although Paul was unmarried, he often considered Timothy his spiritual son and sent him on missionary missions. Their first recorded meeting was in Lystra, and Timothy later followed Paul on his missionary journeys and received guidance from the apostle. Timothy had an important role in strengthening and guiding the early church after Paul. His success in continuing evangelism became fundamental in the history of Christianity. Paul's letters to Timothy, especially 1 and 2 Timothy, became an important part of the New Testament canon and provided guidance for Christians throughout the world. Paul's guidance to Timothy, both while in direct ministry and when Timothy was a leader of the congregation, can be seen in the discipleship messages and teachings delivered, especially in 2 Timothy 3:14-17. This article was researched using historical criticism methods with text research, context and historical analysis behind the writing of the text. At the time this letter was written, Christians were faced with doctrinal and moral attacks from within the church itself. In this text Paul provides advice and guidance to church leaders on how to face these challenges with faith and steadfastness. Here, Paul emphasizes the importance of discipleship and scripture as the basis of the Christian faith. Paul taught Timothy not only to receive teachings, but also to retain and pass them on to others. Discipleship is seen as an ongoing process in the Christian faith, with Scripture as a solid foundation. Paul emphasized that the scriptures were inspired by God and are useful for teaching, reminding, correcting, and training in truth. This shows that true discipleship brings transformation in a person's life and prepares them to serve God effectively.